Karakterisasi dan Kinetika Kalsinasi Dolomit - Winny Wulandari; Subagjo Subagjo; Adnanta Rio; Pratama Istiadi (Jurnal Teknologi Bahan dan Barang Teknik, 2018)
Calcination is a key processing step to increase added value of dolomite to many end-products, including as a feedstock for magnesium metal, as a flux for steelmaking, and refractory bricks. This research dealt with calcination of dolomite from Gresik, East Java. Calcination was carried out in a tubular reactor with a diameter of 3 cm, at an atmospheric pressure and using nitrogen as an elusion gas with the rate of 50 mL/min. Reaction temperature was varied at 700, 800 and 900°C and the reactions were carried out for 1, 2, 3, and 4 hours. The conversion of dolomite calcination reaches 98 to 99% as the calcination conducted at 800 and 900°C. The experimental results were presented using various kinetics models. The diffusion Ginstling-Brounshtein model was found as the best for describing the calcination reaction, which implied the reaction was controlled by internal diffusion of reactants. For the Ginstling-Brounshtein model, the apparent activation energy of dolomite calcination was found to be 77.07 kJ/mol.Kalsinasi merupakan salah satu proses untuk meningkatkan nilai tambah dolomit menjadi berbagai jenis produk akhir, seperti bahan baku pembuatan logam magnesium, sebagai fluks untuk pembuatan baja, serta batu bata tahan api. Penelitian ini dimaksudkan untuk menentukan kinetika kalsinasi dolomit Gresik, Jawa Timur. Temperatur reaksi divariasikan 700, 800 dan 900˚C. Kalsinasi dilakukan selama 1, 2, 3, dan 4 jam di dalam sebuah reaktor tubular dengan diameter 3 cm pada tekanan atmosfer. Reaksi kalsinasi dilakukan dalam kondisi gas nitrogen yang dialirkan sebagai gas-elusi dengan laju alir 50 mL/menit. Konversi dolomit mencapai 98 hingga 99% ketika kalsinasi dilakukan pada temperatur 800 dan 900˚C. Model difusi Ginstling-Brounshtein dapat dijadikan model yang paling sesuai untuk menggambarkan reaksi kalsinasi yang dikendalikan oleh perpindahan massa difusi di dalam partikel. Untuk model Ginstling-Brounshtein, energi aktivasi kalsinasi dolomit terhitung sebesar 77,07 kJ/mol.